TEACHING OF FUNDAMENTAL SCIENCES IN MEDICAL INSTITUTIONS OF HIGHER EDUCATION (Web of Teachers: Inderscience Research, 2024)
An approach is proposed to the implementation of the problems of teaching clinical subjects with the introduction of the courses "Information Technologies in Medicine" and "Biomedical Engineering" based on the following definitions: reasons for the low level of students' knowledge of the method of forecasting; the main contradictions of teaching students the method of analysis; distinctive features of the methodological system of teaching students the modeling method; ways to implement the basic principles of improving educational technologies involving the use of information and communication technologies (ICT) and biomedical engineering (BME) methods; features of ensuring the professional and clinical orientation of communication and engineering training in the medical specialties of universities; fundamentals for the development of methodological support for information, communication and engineering training of the future doctor.